Evaluation of the MYCOPLASMA IST3 urogenital mycoplasma assay in an international multicentre trial. (3rd September 2021) - Boostrom, Ian; Bala, Yohan; Vasic, Jelena Minic; Gluvakov, Jelena; Chanard, Emmanuel; Barratt, Andrew H; Sands, Kirsty; Portal, Edward; Devigne, Laurence; Jones, Lucy C; Spiller, Owen B
Abstract: Objectives: To evaluate the accuracy, susceptibility and specificity of MYCOPLASMA IST3, the next generation of the most popular culture-based in vitro diagnostic device designed to detect, identify and test the susceptibility of urogenital mycoplasma infections. Methods: MYCOPLASMA IST3 was evaluated against culture- and molecular-based gold standard methodologies to detect, identify, enumerate and determine antimicrobial resistance for Mycoplasma hominis and Ureaplasma species in 516 clinical samples collected across France, Serbia and the UK. Sample types included vulvovaginal/endocervical or urethral swabs (dry swab or eSwab ® ), semen and urine samples, which included blinded analysis following addition of a panel of 80 characterized control strains. Results: Overall species identification was excellent for both Ureaplasma spp. (98.4% sensitivity, 99.7% specificity) and M. hominis (95.7% sensitivity, 100% specificity) relative to combined colony morphology on agar and quantitative PCR standards. Non-dilution-based bacterial load estimation by the assay was accurate between 83.7% ( M. hominis ) and 86.3% ( Ureaplasma spp.) of the time (increased to 94.2% and 100%, respectively, if ±10-fold variance was allowed) relative to colonies counted on agar. Resistance accuracy for Ureaplasma spp. varied from gold standards for only 11/605 of individual tests (major error rate = 1.8%) and for 14/917 individual tests for M. hominis (major error rate = 1.5%). Conclusions: The redesigned MYCOPLASMA IST3 assay eliminated previous shortcomings by providing independent accurate resistance screening of M. hominis and Ureaplasma species, even in mixed infections, with CLSI-compliant thresholds. Specificity, sensitivity and enumeration estimates correlated closely with the confirmatory methods.